Scaling-Up Exclusive Breastfeeding Support Programmes: The Example of KwaZulu-Natal - Desmond, Chris (Public Library of Science, 2008)
BACKGROUND: Exclusive breastfeeding (EBF) for six months is the mainstay of global child health and the preferred feeding option for HIV-infected mothers for whom replacement feeding is inappropriate. Promotion of community-level EBF requires effective personnel and management to ensure quality counselling and support for women. We present a costing and cost effectiveness analysis of a successful intervention to promote EBF in high HIV prevalence area in South Africa, and implications for scale-up in the province of KwaZulu-Natal. METHODS AND FINDINGS: The costing of the intervention as implemented was calculated, in addition to the modelling of the costs and outcomes associated with running the intervention at provincial level under three different scenarios: full intervention (per protocol), simplified version (half the number of visits compared to the full intervention; more clinic compared to home visits) and basic version (one third the number of visits compared to the full intervention; all clinic and no home visits). Implementation of the full scenario costs R95 million ($14 million) per annum; the simplified version R47 million ($7 million) and the basic version R4 million ($2 million). Although the cost of the basic scenario is less than one tenth of the cost of the simplified scenario, modelled effectiveness of the full and simplified versions suggest they would be 10 times more effective compared to the basic intervention. A further analysis modelled the costs per increased month of EBF due to each intervention: R337 ($48), R206 ($29), and R616 ($88) for the full, simplified and basic scenarios respectively. In addition to the average cost effectiveness the incremental cost effectiveness ratios associated with moving from the less effective scenarios to the more effective scenarios were calculated and reported: Nothing – Basic R616 ($88), Basic – Simplified R162 ($23) and Simplified – Full R879 ($126). CONCLUSIONS: The simplified scenario, with a combination of clinic and home visits, is the most efficient in terms of cost per increased month of EBF and has the lowest incremental cost effectiveness ratio.